(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
You wouldn’t buy a ticket to a movie if the trailer was awful, right? Therefore, when non-Indigenous people only catch superficially boring glimpses of Aboriginal History, it’s no surprise they grow apathetic towards learning more. This essay explores why a powerful history is still being told so badly.